Primate Populations in Logged and Primary Forests of Sungai Lalang Forest Reserve, Selangor - Silang, Sundai (2001)
The primate study was conducted in Sungai Lalang Forest Reserve, Selangor. The objective of this study was to examine the characteristics of the primate populations in recently and old selectively logged forests, and to compare the populations with those in a primary forest. Three different areas were selected: Primary forest (VJR), Ten-year-old logged forest (Compartment 33 (C33)) and Five-year-old logged forest (Compartment 18 (C18)). Distance Sampling using line transect method was used. Transect surveys were carried out for ten days in each area per month, from October 1998 - April 1999 for a total surveyed distance of 129.6 km. From the results, a total of 183 observations comprising five different species of primates were recorded. The Presbytis melalophos and Presbytis obscura were frequently found in the two logged forests. On the other hand, Hylobates far was frequently observed in C33, while Macaca nemestrina was more abundant in C 18. Meanwhile, the Macaca fascicularis was observed once and only in C 18.